APPLICATION OF BUDDHIST DHARMA PRINCIPLES TO PROMOTE SUSTAINABLE WELL-BEING ORGANIZATION: CASE STUDY OF WAT SAWANG AROM UNDER PHRA NAKHON SI AYUTTHAYA PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Woraphatsorakul, Wariyaphat; Nilkote, Reongwit; Rueangsri, Wongsiri; Sukpom, Thitiwas; Saisena, Natthapat (Journal of Buddhist Anthropology, 2023)
Background and Objectives: Educational institutions are spiritual incubators for young people to become good citizens of the country. The administration must give importance to society, atmosphere and environment to facilitate all-round learning and happiness for all stakeholders. This research article aims to study the concept of sustainable development of well-being organizations according to the Buddhist Dharma principles and propose guidelines for applying Buddhadharma principles to promoting sustainable well-being organizations in the context of educational institutions. Methodology: This qualitative research collected data from relevant documents, relevant documents, group discussions, in-depth interviews, and participatory observations. Main Results: The following results were found: 1) The concept of developing a sustainable well-being organization according to the Buddhist Dharma found that the Buddhadharma principle aimed to develop a healthy life that would lead to complete happiness, relationships in the organization or society and would develop into a well-being organization, and 2) Guidelines for applying Buddhadharma principles to promoting sustainable well-being organizations in the context of educational institutions encompassed the principle of Kalyāṇamittatā, a Buddhist principle that promoted educational institutions as a well-being organization. There were seven elements: Piyo or endearing, Garu or respectable, Bhāvanīyo or emulable, Vattā ca or being a counselor, Vacanakkhamo or being a patient listener, Gambhīrañca Kathaṁ Kattā or being able to deliver deep discourses and No caṭṭhāne Niyojaye or not leading or spurring on to a useless end. It was found that these six principles of Sāraṇīyadhamma should be applied: Mettākāyakamma, which implied to be amiable in deed, openly and in private, Mettāvacīkamma, which implied to be amiable in word, openly and in private, Mettāmanokamma, which implied to be amiable in thought, openly and in private, Sādhāraṇabhogitā, which implied to be sharing any lawful gains with virtuous fellows, Sīlasāmaññatā, which implied to be keeping without blemish the rules of conduct along with one's fellows, openly and in private, Diṭṭhisāmaññatā, which implied to be endowed with right views along with one's fellows, openly and in private. Involvement to Buddhadhamma: A well-being organization is defined as a workplace or educational establishment where all personnel, including students, must be physically healthy. The result is to coexist happily with all members and create a culture of happiness. The concept is in line with the Buddhist goal of developing the individual's potential to become a complete human being. The seven elements of friendship will be applied as a tool to create a good society, and the seven elements of morality will be applied as a tool to create learning and interaction with networks both inside and outside the school to drive the organization towards a perfect well-being organization and a sustainable happiness organization. Conclusions: The "Kalyāṇamittatā Principle" was a Buddhist principle that encouraged personnel in the organization to fulfill their duties. It also affected the creation of a good corporate culture, and the "Sāraṇīyadhamma Principle" was a Buddhadharma principle that aimed to develop the potential of personnel in the organization to be complete and good people. In addition, the Sappurisa-dhamma principle was a fundamental principle for analyzing the members of the organization for assigning tasks appropriately. This was to allow the potential of personnel to carry out the mission of the organization.